Comparison of the efficiency of different enemas on patients with distal ulcerative colitis. (18th January 2019) - Zhang, Yujie; Chen, Di; Wang, Fang; Li, Xiaowei; Xue, Xianmin; Jiang, Mingzuo; Xu, Bing; Chu, Yi; Wang, Weijie; Wu, Kaichun; Mao, Ren; Shen, Jun; et al.
Abstract: Objectives: Rectal application of steroids and 5‐aminosalicylic acid (5‐ASA) is associated with few side effects and has a high therapeutic efficacy in left‐sided colitis. Previous studies have shown that rectal administration of both steroids and 5‐ASA is superior to one single alone. However, some reports are still controversial. Therefore, it is necessary to investigate the treatment choice and efficacy of these different enemas in distal ulcerative colitis (UC) patients. Materials and Methods: Questionnaire survey and a retrospective study were carried out in Chinese hospitals to investigate the efficacy of 5‐ASA or hydrocortisone/dexamethasone or their combination enema in patients with distal active UC. Dextran sodium sulphate (DSS)‐induced colitis model in mice was also utilized to evaluate the effects in vivo. Results: The results from questionnaire survey showed that majority of physicians would prefer oral 5‐ASA with topical 5‐ASA therapy for distal UC patients. However, 43.01% of physicians would like to choose oral 5‐ASA and topical hydrocortisone/dexamethasone with or without 5‐ASA enema. A retrospective study demonstrated that 5‐ASA enema or 5‐ASA combined with hydrocortisone/dexamethasone enema therapy was superior to hydrocortisone/dexamethasone enema to decrease C‐reactive protein, erythrocyte sedimentation rate (ESR), Mayo score and induce clinical remission and clinical response. No superiority of combination therapy was further proved in DSS‐induced colitis in mice. Conclusions: Although 43.01% of physicians would like to choose hydrocortisone/dexamethasone with or without 5‐ASA enema for the treatment of distal UC, the combination was not superior to 5‐ASA enema. Hydrocortisone/dexamethasone enema with 5‐ASA enema is not recommended for distal active UC patients.